DETECTION OF EXTENDED SPECTRUM OF β-LACTAMASE IN FEACAL ESCHERICHIA COLI FROM HUMAN, CATTLE AND CHICKEN IN ONDO STATE, NIGERIA - A. K, ONIFADE,; U. O, INEGBU,; D. O., FADIPE (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The presence of Extended Spectrum β-lactamase (ESBL) was assayed by the double disk synergy test using Amoxicillin-clavulanic acid, Cefoxitin, Ceftriaxone and Ceftazidime. Of the four antibiotics used against the 60 β-lactamase-producing E. coli isolates, 57 (95%) isolates showed the highest susceptibility/synergy to Cefoxitin, followed by Ceftriaxone 56 (93.3%), and Amoxicillin-clavulanic acid 49 (81.7%), while all the isolates were resistant to Ceftazidime (less 18 mm). Plasmid analysis carried out on all the ESBL -producing isolates showed that forty-five isolates were plasmid positive, while fifteen (15) isolates were chromosomal borne. Some of the isolates carried multiple plasmids, while some carried single plasmid. Twelve of the isolates each harboured a set of three plasmids. Four isolates harboured two plasmids each, while twenty-six isolates harboured single plasmids. However, the use of antimicrobial agents regarded as critically or highly important for use in humans should be avoided or minimized in food animals, to preserve the efficiency of these antimicrobial agents for the treatment of infection in humans.